2022
DOI: 10.3390/ijms23158169
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Domain Organization and Regulatory Mechanism of Cystathionine Beta-Synthase from Toxoplasma gondii

Abstract: Cystathionine beta-synthase (CBS) is a key regulator of homocysteine metabolism. Although eukaryotic CBS have a similar domain architecture with a catalytic core and a C-terminal Bateman module, their regulation varies widely across phyla. In human CBS (HsCBS), the C-terminus has an autoinhibitory effect by acting as a cap that avoids the entry of substrates into the catalytic site. The binding of the allosteric modulator AdoMet to this region alleviates this cap, allowing the protein to progress from a basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…We recently demonstrated that T. gondii encodes both the CBS (TgCBS) and CGL (TgCGL) enzymes of reverse transsulfuration (Conter et al, 2020(Conter et al, , 2022Fern andez-Rodríguez et al, 2021;Maresi et al, 2018). TgCGL (UniProtKB A0A125YN40, 46 kDa) shares a high amino acid identity with its homologs from Trypanosomes and Leishmania parasites (58% homology) but is less similar to the human and yeast counterparts (40% and 37% for H. sapiens and S. cerevisiae, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that T. gondii encodes both the CBS (TgCBS) and CGL (TgCGL) enzymes of reverse transsulfuration (Conter et al, 2020(Conter et al, , 2022Fern andez-Rodríguez et al, 2021;Maresi et al, 2018). TgCGL (UniProtKB A0A125YN40, 46 kDa) shares a high amino acid identity with its homologs from Trypanosomes and Leishmania parasites (58% homology) but is less similar to the human and yeast counterparts (40% and 37% for H. sapiens and S. cerevisiae, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…1,6,8,9,26,27 CBS from T. gondii provides a particularly valuable model for exploring the enzyme-substrate specificity because it similarly processes both L-Ser and L-OAS for β-replacement activity to produce L-Cth. [10][11][12] Our analysis of a representative group of 11 prokaryotic and eukaryotic CBSs and OCBSs, for which substrate preference is known, revealed that the polar residues Ser82, Tyr158, and Tyr248 (numbered according to the conventional yeast CBS) are conserved among canonical CBS sequences, while distinct hydrophobic residues (Ala, Phe, and Val) are usually found in OCBSs. Considering the proposal of Devi et al, this provides indirect support that these positions play critical roles in defining the L-Ser/L-OAS preference of the two proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Absorption spectra were recorded on a Jasco V-750 spectrophotometer in a buffer containing 20 mM sodium phosphate pH 8.5 at 25 C using a protein concentration of 12 μM. 10,11 CD spectra were recorded on a Jasco J-1500 CD spectropolarimeter equipped with a Peltier-type temperature controller as previously described. 16,17 Briefly, near UV-Vis (250-600 nm) spectra of 1 mg/mL TgCBS variants were recorded in 1-cm path length quartz cuvette at a scan speed of 50 nm/min.…”
Section: Spectroscopic Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…DSC experiments were conducted using a nano-DSC (TA instrument) with a cell volume of 300 μL. 58 Protein samples, containing 60–80 μM Cyp in 5 mM Hepes, pH 8.0; 10 mM NaCl; and 0.2% ethanol, in the presence or absence of CsA, were heated from 15 to 100 °C at a scan rate of 60 °C h –1 . Data were fitted according to a two-state model using NanoAnalyze software (TA instrument).…”
Section: Methodsmentioning
confidence: 99%